Phenotypic effects of dietary stress in combination with a respiratory chain bypass in mice. Issue 13 (2nd July 2019) - Dhandapani, Praveen K.; Lyyski, Annina M.; Paulin, Lars; Khan, Nahid A.; Suomalainen, Anu; Auvinen, Petri; Dufour, Eric; Szibor, Marten; Jacobs, Howard T.
Abstract: The alternative oxidase (AOX) from Ciona intestinalis was previously shown to be expressible in mice and to cause no physiological disturbance under unstressed conditions. Because AOX is known to become activated under some metabolic stress conditions, resulting in altered energy balance, we studied its effects in mice subjected to dietary stress. Wild‐type mice ( Mus musculus, strain C57BL/6JOlaHsd) fed a high‐fat or ketogenic (high‐fat, low‐carbohydrate) diet show weight gain with increased fat mass, as well as loss of performance, compared with chow‐fed animals. Unexpectedly, AOX‐expressing mice fed on these metabolically stressful, fat‐rich diets showed almost indistinguishable patterns of weight gain and altered body composition as control animals. Cardiac performance was impaired to a similar extent by ketogenic diet in AOX mice as in nontransgenic littermates. AOX and control animals fed on ketogenic diet both showed wide variance in weight gain. Analysis of the gut microbiome in stool revealed a strong correlation with diet, rather than with genotype. The microbiome of the most and least obese outliers reared on the ketogenic diet showed no consistent trends compared with animals of normal body weight. We conclude that AOX expression in mice does not modify physiological responses to extreme diets. Abstract : AOX‐expressing mice reared on high‐fat or ketogenic diet show similar patterns of weight gain and altered body composition as wild‐type mice. Prolonged ketogenic diet impairs cardiac function in both AOX and control mice. Microbiome analysis shows stronger correlations with ketogenic diet, rather than with AOX expression or extent of weight gain per se.